Handling Of Crime Case Relating To The Land By A Police Investigator - Sigit Prihanto (Jurnal Daulat Hukum, 2018)
Handling the criminal case related to the land both by investigators, prosecutors and judges must advance the exact seat keperdataannya legal status. The handling of criminal cases the object of land should be done carefully and cautiously through the understanding of the anatomy of the case and from the evidence of civil owned by the parties. It aims to prevent the engineering / coercion case which is basically a pure civil dispute, eventually used as criminal assault. To deal with this phenomenon, law enforcement agencies have issued policies on formulatif / legislation containing about pending examination of crime related / object land. At the level of the Supreme Court there is a Supreme Court Regulation No. 1 of 1956 and the Supreme Court Decision Number 628K / Pid / 1984. At the level of the Attorney General has issued Circular Letter of the Attorney General for General Crimes No. B-230 / E / EJP / 01/2013. While in the police has been no regulatory policies relating thereto. However, in practice the investigators make policies and regulations issued by the Supreme Court and the Attorney General as guidance in handling the criminal case related to the land. It is for the sake of effectiveness and efficiency in the framework of an integrated criminal justice system. While in the police has been no regulatory policies relating thereto. However, in practice the investigators make policies and regulations issued by the Supreme Court and the Attorney General as guidance in handling the criminal case related to the land. It is for the sake of effectiveness and efficiency in the framework of an integrated criminal justice system. While in the police has been no regulatory policies relating thereto. However, in practice the investigators make policies and regulations issued by the Supreme Court and the Attorney General as guidance in handling the criminal case related to the land. It is for the sake of effectiveness and efficiency in the framework of an integrated criminal justice system.Keywords: Offense; Land; Police.